Landscape diversity and crop vigor outweigh influence of local diversification on biological control of a vineyard pest. Issue 4 (3rd April 2017) - Wilson, Houston; Miles, Albie F.; Daane, Kent M.; Altieri, Miguel A.
Abstract: The influence of local and landscape habitat diversification on biological control of the Western grape leafhopper ( Erythroneura elegantula Osborn) by its key parasitoids Anagrus erythroneurae S. Trjapitzin & Chiappini and Anagrus daanei Triapitsyn was studied in wine grape vineyards. At the landscape scale, Anagrus rely on alternative host species in non‐crop habitats outside of the vineyard to successfully overwinter, while at the local scale vineyard diversification can provide resources, such as shelter and floral nectar, which improve parasitoid performance. In a two‐year experiment, plots with and without flowering cover crops were compared in vineyards representing a gradient of landscape diversity. While the cover crops did attract natural enemies, their populations were unchanged in the crop canopy and there was no difference in parasitism rate, leafhopper density, crop quality, or yield. Vineyards in diverse landscapes had higher early‐season abundance of Anagrus spp., which was linked to increased parasitism and decreased late‐season populations of E. elegantula . Leafhopper densities were also positively associated with crop vigor, regardless of landscape or cover crops. Flowering cover crops did increase abundance of some natural enemy species as well as parasitism rate in vineyard landscapes with intermediate levels of diversity, indicating a local × landscape interaction, although this did not lead to reductions in E. elegantula densities. These findings indicate that, in this agroecosystem, landscape diversity mediates and in many ways outweighs the influence of local diversification and that E. elegantula densities were regulated by a combination of biological control and crop vigor.